Penatalaksanaan Fisioterapi Pada CapsulitisAdhesiva Dextra Di RST Dr Soedjono Magelang - Heroika, Gema, Isnaini Herawati, S.Fis. M.Sc (2016)
Background: Adhesiva capsulitis is a disorder of the shoulder joint that causes pain and limitation of motion due to myofascial disorders. Aspects of physiotherapy with shoulder pain cases the condition is capsulitis adhesiva physiotherapists play a role in pain reduction, increasing the area of motion (LGS), prevent further stiffness and restore muscle strength and improve functional activities Purpose: To investigate the implementation of physiotherapy in reducing pain, increasing range of motion, prevent stiffness further and restore muscle strength and improve functional activities in cases of capsulitis adhesiva using modalities Short Wave Diathermy (SWD), Therapeutic Manipulation and Therapeutic Exercise active exercise using weights and Codman pendulum exercise Results: After treatment for 6 times the results obtained pain assessment in silent pain T1: 1 to T6: 0, tenderness T1: 3 to T6: 1, painful motion T1: 4 to T6: 2; increase the range of motion S: T1: 40-0-90 be T6: 43-0-100, F: T1: 80-0-40 be T6: 95-0-45, R (F = 90): T1: 33 -0-39 be T6: 39-0-42; an increase in the strength of the extensor muscles T1: 2 to T6: 4, flexors T1: 3 to T6: 4, adductor T1: 3 to T6: 4, adductor T1: 2 to T6: 4, eksorotasi T1: 2 to T6: 3, endorotasi T1 : 2 to T6: 3; improvement in functional ability with SPADI with the results of T1: 50 to T6: 42 Conclusion: Short Wave Diathermy (SWD) can reduce pain in conditions Capsulitis Adhesiva, manipulation therapy and exercise therapy can reduce pain and improve LGS, and improve functional ability on the condition capsulitis adhesiva dextra